FOMO syndrome and degeneration of written language in elementary school students - Marisol Yana Salluca (2019)
The research was aim to determine the degree of relationship between syndrome FOMO (Fear of missing out) and written language students of Secondary Educational Institution “José Antonio Encinas” of Juliaca city, 2017. They used the descriptive-correlational design of such non-experimental, positivist paradigm and approach quantitative. The sample was intentional and not probabilistic, made up of students from the fifth grade of secondary, the which they were evaluated with instruments: the questionnaire Fear of missing out syndrome to measure syndrome Fear of missing out and a second questionnaire to measure written language. At the end of the investigation it was identified that the students present Fear of missing out syndrome, very frequently at a very high level, with a frequency that represents 41.37%. Likewise, it has been identified that 63% of students do not respect the spelling regulations, all evidenced in the level of use of the written language Chat. The results indicate that there is r = 0.89 **, of correlation between the two variables, which implies a high positive relationship between Fear of missing out syndrome and written language.